2020
DOI: 10.4265/bio.25.179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Legiolert for Quantification of <i>Legionella pneumophila</i> from Bath Water Samples

Abstract: Monitoring of Legionella pneumophila populations in environmental water is very important for public health, because the bacterium is the primary cause of Legionnaires' disease. The conventional plate culture method, similar to ISO 11731 (2017) , is generally used to enumerate Legionella spp. in water samples. The method, however, is highly complicated and requires sample handling and colony identification skills due to the growth of non-target bacteria and fungi on the agar plates. Thus, the development of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Particularly, all 9 false positive samples were taken from small wells. Relatively high specificity of Legiolert is comparable to other published studies ( Sartory et al 2017 ; Petrisek & Hall 2018 ; Spies et al 2018 ; Inoue et al 2020 ; Scaturro et al 2020 ). It should be noted that those studies performed secondary confirmations by sub-culture.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Particularly, all 9 false positive samples were taken from small wells. Relatively high specificity of Legiolert is comparable to other published studies ( Sartory et al 2017 ; Petrisek & Hall 2018 ; Spies et al 2018 ; Inoue et al 2020 ; Scaturro et al 2020 ). It should be noted that those studies performed secondary confirmations by sub-culture.…”
Section: Resultssupporting
confidence: 89%
“…The manufacturer claims that there is no need for further verification for L. pneumophila due to the high selectivity against non-pneumophila species. More recently, research groups from Europe and the United States have reported that Legiolert yielded a higher sensitivity (i.e., higher counts of correctly identified positive samples) and had a higher specificity (i.e., higher counts of correctly identified negative samples) for L. pneumophila compared with the conventional BCYE agar method ( Sartory et al 2017 ; Petrisek & Hall 2018 ; Spies et al 2018 ; Inoue et al 2020 ; Scaturro et al 2020 ). While this method shows promising practical applications (i.e., simplistic and less laborious) over the traditional culture method, further testing against various types of environmental water samples is necessary to ensure its reliability.…”
Section: Introductionmentioning
confidence: 99%
“…This study confirms results reported from 10 previous studies using Legiolert, indicating this method works as well or better than BCYE‐based methods for recovery and detection of L. pneumophila in water samples: cooling towers (Barrette, 2019); drinking water in distribution systems (LeChevallier, 2019a, 2019b); public bathing water and hot springs (Inoue et al, 2020), potable and nonpotable (Monteiro et al, 2021; Petrisik & Hall, 2018); nonpotable, cooling towers (Rech et al, 2018); building potable and nonpotable (Sartory et al, 2017); potable water (Scaturro et al, 2020); and building potable and nonpotable (Spies et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…One study using Legiolert in water distribution systems reported false positives due to Brevundimonas vesicularis, B. diminuta, Sphingomonas koreensis, Ochrobactrum intermedium and Elizabethkingia anophelis (LeChevalier 2019). In public bath water samples, false positivity was noted for Legiolert with two Pseudomonas species (P. otitidis and P. mendocina) and S. marcescens (Inoue et al 2020). These organisms, and other species of these genera, can be regularly found in drinking water and also be opportunistic human pathogens of potential concern to immunocompromised individuals (Koskinen et al 2000;Szymanska 2007;Ryan and Adley 2010;Lee et al 2011;Lau et al 2016;Bharucha et al 2017;Kyritsi et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…otitidis and P. mendocina ) and S. marcescens (Inoue et al . 2020). These organisms, and other species of these genera, can be regularly found in drinking water and also be opportunistic human pathogens of potential concern to immunocompromised individuals (Koskinen et al .…”
Section: Resultsmentioning
confidence: 99%